International Momentum Strategies - Rouwenhorst, K. Geert (Journal of Finance, 1998)
International equity markets exhibit medium‐term return continuation. Between 1980 and 1995 an internationally diversified portfolio of past medium‐term Winners outperforms a portfolio of medium‐term Losers after correcting for risk by more than 1 percent per month. Return continuation is present in all twelve sample countries and lasts on average for about one year. Return continuation is negatively related to firm size, but is not limited to small firms. The international momentum returns are correlated with those of the United States which suggests that exposure to a common factor may drive the profitability of momentum strategies.